EXPERIMENTAL STUDIES OF DYNAMIC LOADS IN THE LIFTING DRIVE OF A SINGLEGIRDER BRIDGE CRANE - STRELBITSKYI, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Single-girder overhead cranes play an important role in the logistics infrastructure of port warehouses, ensuring efficient handling and movement of good. Their design, consisting of a single load-bearing beam supported by end trolleys, allows for optimal space utilization and adaptation to different layouts. It is known that during the operation of cranes, when loads are lifted, significant dynamic loads are applied to the ropes. This, in turn, causes additional forces in the hoisting drive, which can potentially lead to its rapid wear and breakdown. Given their key role in the technological cycle, the stability and uninterrupted operation of these systems critically affect the efficiency of port lines. A review of the literature has revealed that dynamic phenomena in load lifting mechanisms have been insufficiently studied. It was found that the actual mechanisms of machines are often reduced to elementary calculation schemes, and the resulting mathematical models are generalized and do not take into account the unique features of the functioning and design of specific cranes.The aim of the study is to experimentally investigate the dynamic loads in the ropes of the single-girder crane lifting drive, taking into account the peculiarities of operation. For the study, 4 identical 6-ton hook cranes were selected, which had been in operation in warehouses for more than 12 years and had been handling steel coils. The performance and manufacturing time of the cranes differed slightly. To analyze the dynamic forces in the drive elements, the strain-gauge method was used. The analysis of the data obtained showed that the change in the force in the rope branch over time is oscillatory. The calculated dynamism coefficients for lifting loads from 2 tons to 6 tons vary from 1.11 to 1.34. The analysis of the data obtained shows that the loads in the rope branches that occur during braking do not exceed those observed during the initial lifting of the load from the base. The results of the study can be useful for refining existing models and developing new dynamic models of overhead cranes.